Fatores associados ao desenvolvimento de sepse, maior tempo de internação e mortalidade hospitalar em crianças e adolescentes submetidos à cirurgia cardíaca - Alves, Débora Santana (2022)
Introduction: Heart disease is present in 1 to 3% of live births and is a major cause of heart surgery in this population. The cardiac surgical procedure can lead to several clinical complications that can seriously compromise child health and development, such as higher hospital stay, development of nosocomial infection/sepsis or even death. In addition to being scarce, studies that assess these outcomes do so in isolation or without considering some variables that are known to be associated with them in the analysis. Thus, further investigations are needed on the subject, considering more complete and dynamic models, such as structural equation modeling. Objective: To analyze factors associated with the development of sepsis, higher hospital stay and mortality in children and adolescents undergoing cardiac surgery. Material and Method: A retrospective documentary-based study was carried out from 2014 to 2018 with all children and adolescents (0 to 18 years old) who underwent cardiac surgery during hospitalization (n=237). Clinical, demographic, anthropometric and biochemical data were collected from the electronic medical record. Elaboration of a conceptual model and subsequent analysis of structural equations were performed to estimate the association between demographic, clinical, biochemical factors, nutritional status and the outcomes sepsis, length of hospital stay and death. Results: Of the 237 patients included in the study, the frequency of sepsis, prolonged hospitalization (≥ 30 days) and death was 5.5%(13), 15.2%(36) and 39.2%(93), respectively. Multimorbidity was directly associated with the development of sepsis (β = 1.810, p < 0.001). Nutritional status (malnutrition) was associated with increased length of hospital stay (β = 0.468, p < 0.001), as well as multimorbidity (β =1.281, p < 0.001). Length of stay (β = -0.113, p = 0.004) and hemoglobin levels were inversely associated (β= -0.113, p=0.004), while sepsis was directly associated (β =0.629, p < 0.001) with mortality. hospital. Finally, age was inversely associated with nutritional status (malnutrition-β = -0.112, p <0.001). Conclusion: Multimorbidity was associated with sepsis and higher hospital stay and malnutrition. Decreased hemoglobin, the presence of sepsis, and higher hospital stay were associated with in-hospital mortality in pediatric patients undergoing cardiac surgery.